Motherwort Injection for Preventing Uterine Hemorrhage in Women With Induced Abortion: A Systematic Review and Meta-Analysis of Randomized Evidence - Xinyu, Xue; Xintong, Tang; Youping, Li; Feng, Wan; Jiajie, Yu (Frontiers in Pharmacology, 2022)
Objective: Motherwort injection (MI) is a modern patented injection extracted from motherwort. Empirical studies and systematic reviews have shown the benefits of motherwort injection for preventing postpartum hemorrhage after vaginal delivery and cesarean section. This study aimed to explore the efficacy and safety of motherwort injection for the prevention of post-abortion uterine hemorrhage. Methods: A comprehensive literature search was conducted to identify RCTs regarding the effect of the use of motherwort injection in women after abortion. Data from trials were pooled by meta-analysis and a random-effects model was used to calculate the summarized relative risks (RRs) and their 95% CIs. The grading of recommendations assessment, development, and evaluation (GRADE) methodology was used to access the quality of the evidence. Results: Nine trials with 1675 participants were identified. MI combined with oxytocin compared to oxytocin had a significantly lower blood loss within two hours (MD: −50.00, 95% CI −62.92 to −37.08) and within 24 hours (MD: −50.00, 95% CI −62.92 to −37.08); there was no significant difference between MI and oxytocin(24 h: MD: 0.72, 95% CI -7.76 to 9.20; 48 h: MD: -0.01, 95% CI -11.35 to 11.33; 72 h: MD: -1.12, 95% CI -14.39 to 12.15). Compared with oxytocin or no intervention, both MI and MI combined with oxytocin had a significantly decreased duration of blood loss (MI vs. O: MD -2.59, 95% CI -4.59 to -0.60; MI+O vs. O: MD -2.62, 95% CI -3.02 to -2.22; MI+O vs. No intervention: MD -1.80, 95% CI -2.28 to -1.33). Seven trials reported adverse event outcomes. Three cases were found in the MI group, and five induced abortion syndromes were found in the combined group. 29 adverse events were reported in the oxytocin group instead. The recovery time of normal menstruation was significantly earlier in the group using MI compared with oxytocin (MD: -3.77, 95% CI -6.29 to -1.25), and the endometrial thickness in the MI group was significantly different from that in the oxytocin group (MD: 2.24, 95% CI 1.58 to 2.90). Conclusions: Prophylactic use of motherwort injection may reduce the risk of uterine hemorrhage after abortion.